Investigating Employee Perception about Job Insecurity towards Employee Engagement during The Covid-19 in â€œX-Hotelâ€ in Bandung - Jesslyn, Kirby; Abryanto, Rano (Conference Series, 2021)
Orientation, the inter-individual differences of employees might affect their engagement. However, job engagement might also be influenced by job insecurity. Research purposes: The objective of this study was to examine the relationship between job insecurity and job engagement. Motivation for the study: Job engagement leads to positive individual and organizational outcomes, and study on the determinants will give useful information for diagnosis and intervention. Research design, approach and method: A correlational design was used. Survey design was conducted among 110 employees in several departments in the hotel. The measuring instruments included the Psychological Empowerment Questionnaire which includes job description, job commitment, emotional exhaustion, job performance, strategic alignment and job satisfaction. Statistically significant relationships were found between job insecurity and Job engagement have an impact of 5.8%. Thus, also presenting effective information, which of all the indicators has the most effect. Therefore, the result of the research will directly present further information towards the employeesâ€™ perception during the Covid-19 Pandemic by which relates to the future improvement by the organization. The findings imply that initiatives focusing on the job engagement of workers during the pandemic (i.e., meaningfulness, competence, self-determination, and impact) will contribute to employee job engagement (vigor, devotion, and assimilation). When job instability is high, it is critical to focus on employee psychological empowerment.